2017
DOI: 10.18632/oncotarget.15758
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of the relationship of cancer coping self-efficacy with distress and quality of life

Abstract: Self-efficacy for coping with cancer is a specific construct that refers to behaviors that occur in the course of dealing with a cancer diagnosis, cancer treatments, and transitioning to survivorship. One of the more widely used measures of self-efficacy for coping strategies with cancer is the Cancer Behavior Inventory. The following general questions provide a framework for this research: 1. Is self-efficacy for coping with cancer related to distress and quality of life of a cancer patient?. 2. Do self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
120
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 58 publications
18
120
1
2
Order By: Relevance
“…Therefore, results have to be interpreted with caution. However, we could show in line with others, for glioma patients greater SECC to be associated with lower DT and lower frequency of unmet needs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, results have to be interpreted with caution. However, we could show in line with others, for glioma patients greater SECC to be associated with lower DT and lower frequency of unmet needs.…”
Section: Discussionsupporting
confidence: 92%
“…SECC was found to be associated with lower psychological distress in cancer patients . The same association was found in our study: Glioma patients with greater SECC reported lower distress and lower frequency of unmet needs.…”
Section: Discussionsupporting
confidence: 90%
“…This result is completely in line with the social cognitive theory, that posits self-efficacy for coping with cancer in a strict negative relationship with stress and positive relationship with quality of life of cancer patients (21,24). Therefore, also past literature results confirmed these relationships (4,25).…”
Section: Discussionsupporting
confidence: 73%
“…Along those lines, selfefficacy for coping with cancer, that is the expectations about the ability to cope with cancer, plays a critical role in influencing cancer-related outcomes including anxiety, directly or indirectly (4,20,21). There is a negative relationship between perceived self-efficacy for coping with cancer and anxiety in cancer patients (4,(20)(21)(22)(23)(24)(25) and, specifically, in breast cancer patients (4,26). Recently different studies are showing an extension of the role of selfefficacy, specifically in cancer patients, as statistic moderator of the effect of cancer stressors (27), and also in moderating the effect of intervention in breast cancer patients (28).…”
mentioning
confidence: 99%
“…Self-efficacy is the belief that a person can produce desired outcomes as a result of his/her own actions using their own capabilities and skills (Bandura, 1997). People with a high degree of self-efficacy have a greater confidence in their ability to execute courses of action and have a higher probability of attaining their goals (Chirico, Lucidi et al, 2017). Self-efficacy is associated with QoL in general (Kostka & Jachimowicz, 2010) and with QoL outcomes in cancer (Chirico, Serpentini et al, 2017;Foster et al, 2015;Thieme, Einenkel, Zenger, & Hinz, 2017).…”
Section: Introductionmentioning
confidence: 99%